2023
DOI: 10.1088/1757-899x/1285/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic modelling of axial flow-induced vibration (FIV) for nuclear fuel rods

Abstract: Flow-induced vibration (FIV) at the spacer grid in the fuel assembly of a Light Water Reactor (LWR) is the leading cause of fuel failure. This project aims to produce a simulation benchmark on the experimental campaign at MACE on axial FIV of a cantilever beam in an annular tube, that mimics the configuration and environment of a typical LWR. The nuclear fuel rod, which consists of fuel pellets filled in Zirconium alloy cladding is modelled in the experiment as a steel rod filled with lead shots that closely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The URANS model closely matches the experimental results, registering just slightly above the first mode of vibration in still water. This near alignment reflects the limited impact of flow on the vibration frequency, further emphasising their dependence on the rod's properties [9][10][11][12][13][14][15].…”
Section: Fixed-free Configurationmentioning
confidence: 92%
See 3 more Smart Citations
“…The URANS model closely matches the experimental results, registering just slightly above the first mode of vibration in still water. This near alignment reflects the limited impact of flow on the vibration frequency, further emphasising their dependence on the rod's properties [9][10][11][12][13][14][15].…”
Section: Fixed-free Configurationmentioning
confidence: 92%
“…Recent work by Salachna et al (2023) [14] has demonstrated the effectiveness of the URANS Reynolds stress model proposed by Launder, Reece, and Rodi (LRR) [18] in successfully reproducing both the amplitude and the frequency of axial-FIVs observed in experiments with a cantilever rod exposed to turbulent water flow at a Reynolds number of 16.1k [16]. This same methodology was then successfully extended to a higher Reynolds number of 35.1k [15]. This paper further develops the axial-FIV numerical methodology originally proposed by Salachna et al (2023) [14] by expanding the range of Reynolds numbers investigated (up to 61.7k), by incorporating new highresolution experimental data which have been generated specifically to support the further development of the numerical methodology, and by implementing the k-ω SST turbulence model in addition to the URANS LRR model previously employed.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations